Association between point mutations of macrolide-resistant Mycoplasma pneumoniae and clinical antibiotic treatment efficacy: a meta-analysis - Wang, Rutong; He, Junfeng; Feng, Yingqi; Wang, Mengyao; Zhong, Chi; He, Siqin; Tu, Siqi; Wen, Na; Wang, Chuan (Frontiers in Pharmacology, 2025)
BackgroundThe increasing macrolide resistance in Mycoplasma pneumoniae is mainly driven by mutations in the V domain of 23S rRNA (A2063G/A2064G), which impairs the efficacy of first-line treatment. Previous meta-analyses failed to distinguish between mutation subtypes or quantify age-specific susceptibility, blurring the clinical significance of different mutation burdens.ObjectiveTo quantify the differential impact of single mutation (A2063G) and double mutation (A2063G + A2064G) on core clinical outcomes and to dissect the age-adjusted effects between children and adults.MethodsWe searched PubMed, Web of Science, Embase, Scopus, and CNKI databases (up to June 2025). The Newcastle-Ottawa Scale was used to assess study quality. Random-effects models were applied to handle heterogeneity (I2 > 50%), and subgroup analyses were conducted to compare mutation subtypes and age-stratified effects.ResultsA total of 53 studies (n = 8,960 individuals, covering 5 countries) were included. Double mutations significantly prolonged the duration of fever compared to single mutations (HR = 5.32, 95% CI: 4.27–6.61 vs. HR = 3.66, 95% CI: 1.89–7.09; P < 0.001) and were more likely to cause severe illness (HR = 7.80, 95% CI: 2.51–24.18 vs. HR = 5.89, 95% CI: 2.03–17.08). There was no difference in hospital stay between the two mutation subtypes, but both were longer than the wild type (MD = −3.33 days). The duration of fever in children was shorter than that in adults for all genotypes (overall HR = 3.72 vs. 5.52; double mutation HR = 5.37 vs. 5.66; single mutation HR = 3.85 vs. 4.45; all P < 0.01).ConclusionDouble mutations in 23S rRNA are an independent prognostic factor more severe than single mutations, establishing mutation burden as a key predictive indicator for the first time. This study shows that children have a faster resolution of fever in all genotypes, highlighting the regulatory role of host age immunity on outcomes. This study advocates for the detection of mutation subtypes in high-resistance areas to guide early treatment escalation and risk stratification monitoring.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251071963, identifier CRD420251071963.